Prymas, ojciec, pasterz....Role komunikacyjne kardynała Wyszyńskiego - Makuchowska, Marzena (Stylistyka, 2021)
The paper describes the language and stylistic features of Stefan Wyszyński ’s pastorał let- ters, resulting from the communicative roles which were taken by the Primate of Poland. These were the roles of bishop, father, shepherd or prophet, which on the one hand expressed the superior position of the speaker and on the other hand his caring attitude to- wards his addressees. The roles determined an emotional character of persuasive strate- gies as well as the use of the means of high style.